2014
DOI: 10.4161/15548627.2014.984270
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition uncovers the neurotoxic action of the antipsychotic drug olanzapine

Abstract: We investigated the role of autophagy, a controlled cellular self-digestion process, in regulating survival of neurons exposed to atypical antipsychotic olanzapine. Olanzapine induced autophagy in human SH-SY5Y neuronal cell line, as confirmed by the increase in autophagic flux and presence of autophagic vesicles, fusion of autophagosomes with lysosomes, and increase in the expression of autophagy-related (ATG) genes ATG4B, ATG5, and ATG7. The production of reactive oxygen species, but not modulation of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 86 publications
8
57
1
Order By: Relevance
“…Furthermore, the results presented here also showed that AGE-induced autophagy involved mitophagy. This finding is consistent with the proposal suggesting that the ROS generated from damaged mitochondria lead to the collapse of the MMP and a transient increase in ROS generation via the electron transfer chain, which constitutes a positive feedback circle, 24 eventually leading to autophagic clearance of the impaired mitochondria, 42 and a reduction in oxidative stress. 26 In addition to mitophagy, general autophagy confers a cytoprotective role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the results presented here also showed that AGE-induced autophagy involved mitophagy. This finding is consistent with the proposal suggesting that the ROS generated from damaged mitochondria lead to the collapse of the MMP and a transient increase in ROS generation via the electron transfer chain, which constitutes a positive feedback circle, 24 eventually leading to autophagic clearance of the impaired mitochondria, 42 and a reduction in oxidative stress. 26 In addition to mitophagy, general autophagy confers a cytoprotective role.…”
Section: Discussionsupporting
confidence: 92%
“…It is well established that enhanced ROS production induces autophagy, 22, 42, 43 which was confirmed in the present study. We found that treatment with the ROS scavenger NAC reversed LC3 conversion and puncta and decreased p62 expression in AGE-treated cells, suggesting that AGE-induced autophagy was related to ROS accumulation in mesangial cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, this effect may also be due to the anticholinergic or anti-histaminergic effects, or sedation. Recently another atypical antipsychotic drug Olanzapine was shown to exhibit neurotoxic effects by influencing autophagy, demonstrated both in vivo and in vitro [28]. Thus, the potential negative effect of risperidone on AD pathology may be mediated through an effect on autophagy in the neurons.…”
Section: Discussionmentioning
confidence: 99%
“…As an antipsychotic drug, olanzapine mainly targets receptors of neurotransmitters such as dopamine, serotonin (5-HT), and γ-aminobutyric acid (GABA), which have been reported to regulate autophagy [32,40,41]. Further, olanzapine also induces autophagy by activating AMP-activated protein kinase (AMPK) signaling [42,43] and up-regulating the expression of the products of ATG genes such as ATG5 and Beclin-1 [44].…”
Section: Figure 1 Space Of Autophagy Modulators and Their Targets (A)mentioning
confidence: 99%